Regulation of pyroptosis by NF-κB signaling - Yang, Ling; Zhang, Yan; Chai, Zhuodong; Zhou, Yuqi; Li, Zhenyu; Wei, Yinan (Frontiers in Cell Death, 2025)
Pyroptosis is a form of proinflammatory cell death characterized by inflammasome activation, pore formation, and the release of pro-inflammatory cytokines such as interleukin-1β (IL-1β) and IL-18 upon cell rupture. Nuclear factor-κB (NF-κB), a prototypical pro-inflammatory transcription factor, plays a critical role in immune system regulation. Recent research highlights the multifaceted roles of NF-κB signaling in pyroptosis. Various immunologically relevant ligands and their receptors can activate the NF-κB pathway to promote pyroptosis, with Toll-like receptors (TLRs), IL-1 receptors (IL-1Rs), and TNF receptors (TNFRs) being the most prominent. NF-κB regulates the transcription of key components of inflammasomes involved in pyroptosis, particularly the NLRP3 inflammasome. Recent studies also indicate that NF-κB modulates the activation of NLRC4 and AIM2 inflammasomes through distinct pathways in diverse inflammatory conditions, such as acute lung injury and neuroinflammation. Additionally, the NF-κB pathway mediates the production of inflammatory cytokines, including IL-1β, IL-33, and TNF-α, which further regulate pyroptosis. This review examines recent advances in understanding the role of the NF-κB signaling pathway in regulating pyroptosis during infection and inflammation.